Franciscans at prayer - Johnson, Timothy J. (Medieval Franciscans ;, 2007)
Surveying a panorama of medieval Franciscans at prayer, this book offers a nuanced perspective on Franciscan beliefs and spiritual practices that underscores the depth and breath of their mutual passion for the divine and the world they shared.